A novel mitigation technique to eliminate the harmonic effects on over-current relays - Tin, Hillary (Curtin University, 2013)
In this thesis, overcurrent relay performance and relay co-ordination were analyzed with and without the presence of harmonic contents in the power system network using the IEEE 30 bus network. The two analyses proved the different results of overcurrent relay performance under a fault condition. Initially, shunt passive filters were used to overcome the problem, but they become unreliable and active filters were proposed. However, the active filters became dissatisfaction and Hybrid Filters become more in interest. This project implemented and analyzed the Hybrid Filters and its results which were desirable.